Problematika Hukum dalam Penerapan Pasal 109 ayat (1) Undang-Undang Nomor 8 Tahun 1981 tentang Kitab Undang-Undang Hukum Acara Pidana Pasca Putusan Mahkamah Konstitusi Nomor 130/PUU-XIII/2015 Ditinjau dari Putusan Pengadilan Negeri Pekanbaru Nomor: 27/Pid.Prap/2017/PN.PBR - M, Revendra. (Melayunesia Law, 2018)
The legal problem in the application of Article 109 paragraph (1) of the CPC is: the absence of legal sanctions for investigators which does not inform the commencement of the investigation of an incident which is a criminal offense to the prosecutor, the reporter and the victim/complainant; the occurrence of extension to things that become the object of pre-trial; lack of legal protection against the reporter/victim; the absence of the principle of legal fiction by investigators; and not yet optimal method of investigation. The ideal concept of law in the application of Article 109 paragraph (1) CPC is: the existence of legal sanctions for investigators who do not inform the commencement of an investigation of an incident which is a criminal offense to the prosecutor, the reporter and the victim/complainant; the existence of special rules regarding pre-trial object boundaries; optimal and genuine role of the state in providing legal protection to the reporter/victim; law enforcers in the implementation of their main duties and functions shall apply the principles of legal fiction; and changes to the method of investigation so that there is no gap for the suspect to use pretrial facilities in an effort to escape from the law.Â